The Oxbridge-Turin Connection:From Peano and Russell to Bobbio and Hart - Giovanni Battista Ratti (Rivista di Storia dell'Università di Torino)
The article sketches a possible line of development on the Oxbridge-Turin axis from the early analytic philosophy of Peano and Russell to the analytically renewed legal theory of Bobbio and Hart. The paper discusses the different character of the interactions between Russell and Peano and Bobbio and Hart, and then analyzes some of Bobbio’s main critical contributions to the discussion of Hart’s theory on obligation, secondary rules, and the notion of sanction. Finally, it hypothesises that some of the most famous theses of Hart’s theory were briefly anticipated by Bobbio in writings from the late 1950s.